Education, ethno-racial relations and decolonization in the teachers' praxis - Elison Antonio Paim; Patrícia Magalhães Pinheiro; Josiane Beloni de Paula (Universidade Federal de Santa Catarina, 2019)
This article brings theoretical discussions about decoloniality, coloniality - in its triad power, being and knowledge - and racisms. We will emphasize decoloniality as epistemology that ruptures dualisms, comprehend intersections between social identities, and analyzes ethno-racial classifications as the cornerstone of coloniality of power, that is, fundamental to structuring the modern/colonial/capitalist world-system. Thus, we will bring narratives of teachers, who promote debates about the colonialities and racisms present in our society. The article is the result of theses in preparation focusing on the ethno-racial relations in the teachers' formation. We highlight that the praxis of these educational processes is understood here as a decolonial and anti-racist attitude. At this moment, we work with narratives of two teachers in the interface with the thought of decolonials and anti-racists authors.